2004
DOI: 10.1890/03-5133
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Fires, Fungi, and Soil Dynamics in Alaskan Boreal Forests

Abstract: Abstract. Fires are critical pathways of carbon loss from boreal forest soils, whereas microbial communities form equally critical controls over carbon accumulation between fires. We used a chronosequence in Alaska to test Read's hypothesis that arbuscular mycorrhizal fungi should dominate ecosystems with low accumulation of surface litter, and ectomycorrhizal fungi should proliferate where organic horizons are well-developed. This pattern is expected because ectomycorrhizal fungi display a greater capacity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
150
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 197 publications
(162 citation statements)
references
References 65 publications
9
150
0
3
Order By: Relevance
“…Second, compared to brush clearing, controlled burning may change the soil microclimate. Treseder et al (2004) found that after burning T S changes temporarily because of the disappearing of the litter mantle and the darkening of ground. In addition, burning can yield hydrophobic hydrocarbons that, together with the layer of ashes, could limit the soil's water infiltration capacity and hence its moisture content (Neary et al, 1999).…”
Section: Effect Of Controlled Burning On Soil C Releasementioning
confidence: 99%
“…Second, compared to brush clearing, controlled burning may change the soil microclimate. Treseder et al (2004) found that after burning T S changes temporarily because of the disappearing of the litter mantle and the darkening of ground. In addition, burning can yield hydrophobic hydrocarbons that, together with the layer of ashes, could limit the soil's water infiltration capacity and hence its moisture content (Neary et al, 1999).…”
Section: Effect Of Controlled Burning On Soil C Releasementioning
confidence: 99%
“…We collected samples from two sites in east-central Alaska, USA (63155 0 N, 145144 0 W) described in detail by Treseder et al (2004). The first site is a boreal spruce forest that burned in 1999 and is now dominated by shrubs, herbaceous perennials, and small deciduous trees.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Although there is a growing literature on fungal response to wildfire (Dahlberg et al, 2001;Treseder et al, 2004), only one previous set of studies exists in which pre-fire data were available for a wildfire event (Horton et al, 1998;Baar et al, 1999;Grogan et al, 2000), and this was less than a decade after the first application of PCR to the study of fungi (White et al, 1990). All other studies of post-fire ECM fungal recovery have primarily used space-for-time comparison where different aged fires were studied (Buscardo et al, 2010;Kipfer et al, 2011), laboratory heating experiments (Izzo et al, 2006;Peay et al, 2009;Kipfer et al, 2010) or low-intensity prescribed fires where host death was not involved (Stendell et al, 1999;Brown et al, 2013).…”
Section: Introductionmentioning
confidence: 99%